2020
DOI: 10.1039/d0ee01213k
|View full text |Cite
|
Sign up to set email alerts
|

Side-chain tuning in conjugated polymer photocatalysts for improved hydrogen production from water

Abstract: Structure–property–activity relationships in solution processable polymer photocatalysts for hydrogen production from water were probed by varying the chemical structure of both the polymer side-chains and the polymer backbone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 56 publications
11
152
0
Order By: Relevance
“…This is in line with previous observations by Cooper et al. for hydrophilic sulfone containing polymer photocatalysts, [ 67–69 ] where wettability was identified as crucial parameter for electron transfer during proton reduction. Our study demonstrates that interfacial effects in general are a bottleneck reaction, i.e., hole extraction, which is also important to enable efficient charge carrier separation and with it, high HER rates.…”
Section: Resultssupporting
confidence: 93%
“…This is in line with previous observations by Cooper et al. for hydrophilic sulfone containing polymer photocatalysts, [ 67–69 ] where wettability was identified as crucial parameter for electron transfer during proton reduction. Our study demonstrates that interfacial effects in general are a bottleneck reaction, i.e., hole extraction, which is also important to enable efficient charge carrier separation and with it, high HER rates.…”
Section: Resultssupporting
confidence: 93%
“…Previously, we showed that this approach yields results comparable to those measured using photoelectron spectroscopy, at least for amorphous polymers. 54,60 The results of these calculations (Fig. 3d), suggest for MeF1-MeF3 and S1-S3 that with increasing oligomer length the IP becomes less positive and EA less negative, and hence the driving force for triethylamine/Na 2 SO 3 /Na 2 S oxidation and proton reduction decreases with oligomer length.…”
Section: Driving Force Calculationsmentioning
confidence: 92%
“…18,22,23 The dispersability of a polymer probably depends both on the size (distribution) of the polymer particles in suspension and the inherent wettability of the polymer or the sidegroups present. 24,25 Our empirical observations are in line with a classical semiconductor microscopic model where the exciton formed through the absorption of light either (i) spontaneously falls apart and the free electron and hole formed in the process reduce protons/SEA and oxidise water/SED, respectively, or, more likely due to the large exciton binding energy relative to k B T in polymers, (ii) drives one of the two solution half-reactions and the remaining free-electron/hole the other. 26,27 Transient spectroscopy of polymers under hydrogen evolution conditions 25,28 indeed suggest the presence of electron polarons, i.e.…”
Section: Introductionmentioning
confidence: 99%